Mechanical performance of fiber-reinforced concrete and functionally graded concrete with natural and recycled aggregates - Sabireen; Faheem Butt; Afnan Ahmad; Kiffayat Ullah; Osama Zaid; Hammad Ahmed Shah; Tahseen Kamal (Ain Shams Engineering Journal, 2023)
This study aims to assess the mechanical performance of functionally graded concrete (FGC) in comparison to conventional plain cement concrete (PCC) and fibre-reinforced concrete (FRC). For this purpose, five concrete mixes were prepared, defined in eleven patterns, including PCC as a control mix, two FRC mixes, and eight combinations for FGC mixes. The hooked-end steel fibres and recycled thin polyethylene terephthalate (PET) strips from used bottles were utilized as fibres in 0.75 % of the volume of the mix in the FRC and FGC mixes. The natural aggregates were replaced by 15 % by weight with recycled plastic aggregates (RPA) and recycled concrete aggregates (RCA) in the FGC mixes. The mechanical performance of all specimens was assessed by compressive, split tensile and flexural strength tests, whereas the concrete quality was evaluated by the ultrasonic pulse velocity (UPV) test. The results revealed that the FRC mix containing steel fibres has 50.6 % higher compressive strength, while PET-FRC exhibited 42.4 % lower strength than the PCC. The best combination of the FGC mix is RCA + SFRC (H), which showed 27.6 % more compressive strength than PCC. The steel fibre-reinforced concrete (SFRC) mix has the highest split tensile strength, which is 47.5 % higher than the PCC. The best combination of FGC mixes is SFRC + PET-FRC (J), yielding 29.3 % higher tensile strength than PCC. On the other hand, both fibres contribute to the flexural strength enhancement of FRC. The FGC mix (K) yielded the highest flexural strength, with PET-FRC and SFRC in the upper and bottom layers, respectively, giving 40 % more flexural strength than the PCC specimen. The UPV values depicted that fibres and recycled aggregates in FGC specimens enhanced the quality of concrete. The highest value of UPV was recorded in the mix PCC + SFRC (G) containing PCC and steel fibres, which almost reached the upper limit of the recommended UPV values.